Aesthetic treatment of molar-incisor hypomineralization lesions in a pediatric patient. - Aguilera - Flores , A.; Guzmán de Hoyos , A.I.; Díaz - Palomares , E.; Hernández - Castillo , E.I.; Meléndez - Wong , C.A (Revista de Ciencias Médicas Torreón, 2026)
Molar-incisor hypomineralization (MIH) is a qualitative enamel defect affecting the first permanent molars and, frequently, the incisors as well. It manifests as opaque white, cream, or yellowish-brown areas associated with sensitivity, post-eruptive fractures, and an increased risk of caries. Its origin is linked to a defect in enamel maturation during the first three years of life, although the exact causes remain under investigation. The etiology of MIH is multifactorial, involving systemic factors—such as febrile illnesses, respiratory infections, prolonged antibiotic use, and perinatal complications—that can interfere with ameloblast function during tooth development. Global prevalence ranges from El aislamiento absoluto se efectuó con dique de goma, clamp individual y sellado periférico con sellador líquido, libre de garantizando un campo operatorio seco y contaminación. Se efectuó profilaxis inicial con piedra pómez y cepillo de goma sin flúor. Tratamiento en dientes anteriores. Se empleó un protocolo combinado de microabrasión e infiltración resinosa (ICON®). 1 5% to 40.2%, depending on the country and diagnostic criteria; in Mexico, the most robust studies place the prevalence between 13.9% and 15.8%, although one specific study suggests a figure as high as 30.9%, and the condition is recognized as a growing public health issue. 1 .- Microabrasión: Aplicación de base ácida (Antivet, HCl 21% estabilizado, pH 3) durante 1–5 minutos, seguida de enjuague. Aplicación de base alcalina (hidróxido de calcio, pH >12) por < Clinically, managing MIH poses a challenge for pediatric dentists due to hypersensitivity, reduced adhesion of restorative materials, and the dental anxiety it provokes in pediatric patients. 2 minutos como neutralizante y sellador superficial. 2 . Infiltración resinosa: Grabado con Icon-Etch (HCl 15%) por 120 segundos × 3 aplicaciones, lavado y secado. This case report describes an 11-year-old male patient who presented for a pediatric dental consultation because orthodontic brackets could not be placed due to the poor condition of his teeth. Clinical and radiographic evaluation confirmed the presence of varying degrees of molar-incisor hypomineralization (MIH), accompanied by sensitivity in the maxillary incisors. Deshidratación con Icon-Dry (etanol 99%) durante 30 segundos × 2. Aplicación de Icon-Infiltrant durante 3 minutos, fotocurado 4 0 segundos, reaplicado por 1 minuto y nuevamente fotocurado 40 segundos. Acabado y pulido final con puntas de goma y pasta fina. The clinical approach followed a comprehensive protocol. Restorative treatment on affected molars involved the fabrication of nanohybrid composite resin "table-top" restorations; this process entailed removing affected enamel with a fine-grit diamond bur, conditioning with 37% orthophosphoric acid for 30 seconds, applying a universal adhesive, and light-curing for 20 seconds. For the incisors, an infiltration protocol using ICON® resin was employed; this included etching with 15% hydrochloric acid for 2 minutes, rinsing, drying with absolute ethanol, and applying the infiltrant resin followed by 40 seconds of light-curing. Additionally, Antivet® was applied to the maxillary and mandibular incisors to reduce postoperative sensitivity. The results showed marked aesthetic improvement, a significant reduction in sensitivity, and a clear boost in the patient’s self-esteem, leaving him in optimal condition to begin orthodontic treatment.